Breaking down the work from home mindset in a new normal way - MISHRA, DR. RAGHVENDRA K (The journal of contemporary issues in business and government, 2021)
With the shocking arrival of Covid, work from Home or Telework has become a buzzword now. The Global COVID-19 Pandemic has changed the world radically. The ridiculous appearance of the pandemic has brought about a spontaneous change in varying social statuses. New Complexities has been authored which were not there in the past, and therefore, business units are compelled to change the working styles. In the period of social separating and distant working, things have been changed a great deal. The business world in a state of uncertainty and fear are shifting to work from home, as it is the only way left for them in the quest for survival in the era of pandemic. Everyone is moving to telework, some are doing it in a planned manner with proper planning on the other hand others are doing it, because it seems the only left out in the situation of lockdown and isolation. Both the employers and the employees are trying to find out the optimum way out, but it will be too early to reach conclusion that telework is the optimum solution and it will be successful. Work from Home has its own intricacies. The perception of the employees and the employers may or may not change with time but one question is needed to be asked and that is, Is Work from is Home is better solution? Also, we need to know the perception of employees towards work from Home mode of performing Jobs. This Paper tries and evaluate the perception and point of view how the respondents felt about working from. The researcher also tried to have a clear understanding of supporting factors that have mad work from a more tolerable way of working and what works against working from home.